The development of skills in Primary Health Care nurses for coping with social inequalities in health - Carvalho, Nayara Rodrigues; Gomes, Andréia Patrícia; Mendonça, Érica Toledo de; Polati, Amanda Morais; Amaral, Vanessa de Souza; Moreira, Tiago Ricardo; Oliveira, Deíse Moura de (Ciência e Natura, 2022)
The objective of this study was to identify and develop skills with Primary Health Care nurses to work the social inequalities in health. This is a qualitative research based on action-research, performed with six primary health care nurses in a municipality of Minas Gerais, who participated in educational workshops addressing coping strategies for social inequalities in health. The data collection occurred through a focal group and non-participant observation, from March to May 2018. The data were analyzed through the thematic content analysis technique. The identification and training of skills to cope with this was founded on knowledge, skills and attitudes. The participants stressed the importance of knowing their role in the scenario where they work, as well as the functioning of the Health Care Network and legislation to support them to coping with this problem, being the communicational skills essential in this process. The knowledge acquired in the workshop enabled participants to recognize attitudes in their professional routine, which enable them to act in the face of this reality. The present study indicates the importance of appreciating and strengthening the training of nurses for the development of competences to act on social inequalities.